\(\frac{1-x_1}{1+x_2}+\frac{1-x_2}{1+x_1}=\frac{\left(1-x_1\right)\left(1+x_1\right)+\left(1-x_2\right)\left(1+x_2\right)}{\left(1+x_2\right)\left(1+x_1\right)}=\frac{1-x_1^2+1-x_2^2}{1+x_1+x_2+x_1x_2}\)
\(=\frac{2-\left(x_1+x_2\right)^2+2x_1x_2}{3+x_1x_2}=\frac{2x_1x_2-2}{x_1x_2+3}=\frac{4m^2+2}{2m^2-7}\)
Suy ra \(\left(2x_1x_2-2\right)\left(2m^2-7\right)=\left(x_1x_2+3\right)\left(4m^2+2\right)\)
\(\Leftrightarrow x_1x_2\left(4m^2-14\right)-4m^2+14=x_1x_2\left(4m^2+2\right)+12m^2+6\)
\(\Leftrightarrow x_1x_2=\frac{-16m^2+8}{16}=-m^2+\frac{1}{2}\)
Từ đây ta viết được phương trình bậc hai phải tìm theo Thalet đảo.